FUNGSI DAN MAKNA SIMBOLIK KESENIAN JARANAN JUR NGASINAN DESA SUKOREJO KECAMATAN SUTOJAYAN KABUPATEN BLITAR - ZAHROTUL MUFRIHAH, DWI (APRON Jurnal Pemikiran Seni Pertunjukan, 2016)
Abstract   Existence of Jaranan Jur Ngasinan art interesting to searched because relating to the function which were adapted to society’s believe and have meaning about Jenggolo soldier. Based on that background, the researcher make some research questions there are how are function and meaning which are contained in Jaranan Jur Ngasinan art, Sukorejo Village, Sutojoyan Subdistrict, Blitar Regency. There are special purposes from this research for described the function and symbolic meaning of Jaranan Jur Ngasinan art, Sukorejo Village, Sutojoyan Subdistrict, Blitar Regency. Data gained by researcher by using qualitative research. The result which gained by researcher. First Jaranan Jur Ngasinan have function as  ritual facility, presentation of the beauty, a fastener of solidarity community, and media cultural preservation. Second, meaning of Jaranan Jur Ngasinan Sukorejo Village, Sutojayan Subdistrict, Blitar Regency are an honest meaning which is come from the “Jur” word, symbolic meaning from the valor of Jenggolo soldier when search Dewi Sekartaji, and also gained from each scene, perspective of movement, music, the cloth, property, the pattern of floor. Meaning of sesaji related with society’s life and the prayer which is used has meaning an expression of gratitude and appealed an protection to God. From that explanations can be concluded that Jaranan Jur Ngasinan have various function and have symbolic meaning about soldier which also related to values of society culture around there. Keywords : Function, Meaning, Jaranan Jur Ngasinan, Blitar’s art